Combined spinal epidural and epidural volume extension: Interaction of patient position and hyperbaric bupivacaine - Asha Tyagi; Anil Kumar; Gautam Girotra; Ashok Kumar Sethi (Wolters Kluwer Medknow Publications, 2011)
Background : Previous trials have documented failure of block augmentation with epidural volume extension, when applied after the intrathecal injection of hyperbaric bupivacaine was made in sitting position. However, there is no study comparing the effect of change in patient position during block performance, on the results of epidural volume extension. Materials and Methods : The study was conducted in two parts in American Society of Anesthesiologists physical status I or II parturients scheduled for elective cesarean section under regional anesthesia. In the first part, 28 patients were randomized to one of the two groups, depending on whether epidural volume extension was applied following the block in sitting (group SE) or lateral position (group LE) (n=14 each). In the second part of the study another 28 patients were recruited and randomized to receive the block in sitting (group S) or lateral (group L) position (n=14 each), without epidural volume extension. All patients received combined spinal epidural block using needle-through-needle technique with intrathecal injection of 9 mg hyperbaric bupivacaine (0.5%) and 10 μg fentanyl. Epidural volume extension was performed using 5 ml normal saline in groups SE and LE. Results : In the first part of the study, the maximum sensory block level was higher in group LE vs. SE (P<0.05). In the second part of the study, no significant difference was seen in the maximum sensory level between group S and group L (P>0.05). Conclusions : If epidural volume extension is being applied with intention of rapid extension of sensory block when hyperbaric bupivacaine has been injected intrathecally, the combined spinal epidural block should be performed in lateral position rather than in the sitting position.